1985
DOI: 10.1016/0042-6822(85)90207-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and localization of CIV polypeptides

Abstract: In order to detect the structural proteins linked with disulfide bonds, CIV was solubilized and electrophoresed under nonreducing conditions in the first dimension and then under reducing conditions in the second dimension. The viral polypeptides linked originally with disulfide bonds were separated into subunits. The complexes were trimers (P'50) or dimers (P60 and P10). The apparent molecular weights of P81, P53, and P49 changed significantly according to the composition of the lysis buffer used, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…The major polypeptide represents about 40 % of the total viral proteins. Radioiodination of the external polypeptides revealed that P'50 is not directly exposed at the surface of the virus (Cerutti & Devauchelle, 1985. The detection of a high level of identity (more than 95 %) in the amino acid composition of the major capsid proteins of two members (TIV and IV22) of the family Iridoviridae led to the development of a strategy for detecting the major capsid protein of CIV using construction of specific oligonucleotide primers and PCR technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major polypeptide represents about 40 % of the total viral proteins. Radioiodination of the external polypeptides revealed that P'50 is not directly exposed at the surface of the virus (Cerutti & Devauchelle, 1985. The detection of a high level of identity (more than 95 %) in the amino acid composition of the major capsid proteins of two members (TIV and IV22) of the family Iridoviridae led to the development of a strategy for detecting the major capsid protein of CIV using construction of specific oligonucleotide primers and PCR technology.…”
Section: Discussionmentioning
confidence: 99%
“…The major capsid protein of CIV consists of two polypeptides, a 150K protein composed of three identical disulphide-linked subunits of 50K (P'50) and a very similar 50K protein (P50) (Cerutti & Devauchelle, 1985). The major polypeptide represents about 40 % of the total viral proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is in agreement with the data reported in the present study. The MCP of CIV consists of two polypeptides, a 150K protein composed of three identical disulphide-linked subunits of 50K (P'50) and a very similar 50K protein (P50) (Cerutti & Devauchelle, 1985). Radioiodination of the external polypeptides revealed that P'50 is not directly exposed at the surface of the virus (Cerutti & Devauchelle, 1985 …”
Section: Discussionmentioning
confidence: 99%
“…More than 30 polypeptides can be differentiated with 2D gel electrophoresis [2]. The major capsid protein (MCP), P50 (467 amino acids, 51.4 kDa), and that of PBCV-1, Vp54, share ~22% sequence identity [3][4][5]. The published 3D image reconstruction of CIV at 26Å resolution revealed that the protein shell (maximum diameter of 1850Å) consists of 12 pentavalent (pentamer) and 1460 hexavalent (trimer) capsomers, arranged with T=147 (h = 7, k = 7) icosahedral, quasi-equivalent symmetry [6].…”
mentioning
confidence: 99%